PERAN IKHWANUL MUSLIMIN DALAM PERUBAHAN SOSIAL POLITIK DI MESIR - Farida, Umma (LP2M IAIN kUDUS, 2014)
THE IKHWANUL MUSLIMIN’S ROLE IN SOCIOPOLITICAL CHANGE IN EGYPT. This research aims to know the position of the Ikhwanul Muslimin movement which grow and develop in Egypt. Trace the genealogy and the history of the Ikhwanul Muslimin, the concept and movement as well as the Ikhwanul Muslimin figures who influence on socio-political movement in Egypt. In addition to the position description of the Ikhwanul Muslimin, the study also tried to reveal the influence of the Ikhwanul Muslimin against the socio-political changes in the country of Kinanah. Since the founding of the Ikhwanul Muslimin, the political map in Egypt is entering a new chapter. The policy of leaders in power in Egypt is experiencing changes and ups and downs, related to its interaction with the Ikhwanul Muslimin. The interaction between Ikhwanul Muslimin and the Government of Egypt was mapped in two periods: pre-revolution and post-revolution. The Ikhwanul Muslimin and the Government of Egypt often tinged the existence of a conspiracy, suppression, which are then greeted with demonstration and competition power grab.